Why we disagree about the Murray–Darling Basin Plan: water reform, environmental knowledge and the science-policy decision context. Issue 2 (3rd July 2019) - Colloff, Matthew J.; Pittock, Jamie
ABSTRACT: Narratives emerging from the interaction between science and policy set the common language for understanding complex environmental issues. We explore discourses of contestation over a major environmental policy, the Murray–Darling Basin Plan, intended to re-allocate irrigation water to restore the environment in south-eastern Australia. We examine three areas of scientific knowledge and decision-making at the science-policy interface: (1) water accounting and availability; (2) perspectives on ecological change and (3) issues of trust and the management of environmental water. Engagement and communication between scientists, bureaucrats and the public forms the basis for understanding contestation: over different sets of values, expectations of what scientists can deliver, perceptions of risk and uncertainty, interpretation of conflicting messages and economic development versus conservation. The Basin Plan was shaped by institutional processes not designed to account for such differences and has inadvertently promoted contestation through exclusion of world views that do not fit those of the decision makers. We consider how the Basin Plan can be re-framed by changing the values, rules and knowledge that set the decision context. These changes enable the Basin Plan to be re-conceptualised from a problem to be solved to an idea that can mobilise imaginative engagement by agents with diverse perspectives.